Terapias alternativas y complementarias de enfermería en el dolor de parto. - Charco Padilla, Fanny Beatriz (2024)
Pain management during childbirth is a significant concern for both pregnant women and healthcare professionals, as it is an unpleasant sensory and emotional experience. In the field of nursing, alternative and complementary therapies have taken great importance in offering their care with non-drug options and minimally invasive methods and lower risk of side effects. The objective of this review is to analyze alternative and complementary nursing therapies in the reduction of pain during labor; this was done through an exhaustive review of the scientific literature; studies that support the application of these therapies were analyzed, as well as their effectiveness, to be integrated into the care of the patient, improve the management of labor pain and maternal-fetal welfare. The analysis was performed on scientific articles published between 2019 and 2023 in databases such as Redalyc, Dialted, Scielo, Scopus, PubMed, Elsevier, and Google Scholar, thesis repositories of national and international universities, organizations such as WHO, PAHO, and MSP. Based on the results obtained, they indicate that alternative and complementary therapies can be effective in reducing pain and stress during labor, improving the overall birth experience for mothers. However, sometimes, women wish to experience all the sensations and manifestations that justify how they perceive and justify the body's work for the birth and the arrival of the new being. In addition, it highlights the need for more training and awareness among nurses to integrate these practices safely and effectively in perinatal care; among the most common methods, hydrotherapy, aromatherapy, music therapy, massage, exercise with the ball, breathing techniques, have shown significant effectiveness, allowing to create a safe environment, increases the sense of autonomy, control and complete management of the mother in the process, which favors a positive experience of childbirth. This study provides a solid basis for the implementation of alternative and complementary therapies by nurses as an option for managing labor pain, promoting the importance of humanized care focused on maternal and fetal well-being.